Climate change challenges the current conservation strategy for the giant panda. (October 2015) - Shen, Guozhen; Pimm, Stuart L.; Feng, Chaoyang; Ren, Guofang; Liu, Yanping; Xu, Wenting; Li, Junqing; Si, Xingfeng; Xie, Zongqiang
Highlights: Metapopulation capacity is a mechanistic measure of habitat fragmentation. Climate changes lead giant panda habitats to shrink and become fragmented. Climate change reduces the effectiveness of protection more inside reserves than outside. It is essential to integrate natural processes and dynamic threats over individual static reserves. Abstract: The global total of protected areas to conserve biodiversity is increasing steadily, while numerous studies show that they are broadly effective. That said, how will current conservation strategies work, given the current and expected changes to the global climate? The giant panda is a conservation icon and exceptional efforts protect its remaining habitats. It provides a unique case study to address this question. There are many studies on the projected loss of habitats as climate warms, but few consider the geographical arrangement of future habitats, current protected area, and species' dispersal abilities. Most alarmingly, we expect much greater habitat fragmentation after climate change. Here, we combine long-term data on giant pandas with climate-change scenarios to predict future habitat loss and distribution in the Min Shan of Sichuan and Gansu, China. We employ metapopulation capacity as a mechanistic measure of a species' response to habitat fragmentation. The results show that climate changes will lead to 16.3 ± 1.4 (%) losses of giant panda habitats. Alarmingly, 11.4% of the remaining habitat fragments would be smaller than the extinction threshold area as the extent of fragmentation increases nearly fourfold. The projected fragmentation of giant panda habitats predicts 9% lower effectiveness inside the protected area network compared with that outside of reserves. A 35% reduction will occur in future effectiveness of reserve networks. The results challenge the long-term effectiveness of protected areas in protecting the species' persistence. They indicate a need for integrating both natural processes and dynamic threats over a simple reliance on individual static natural reserves.